Distinct dynamic regulation of pectoralis muscle metabolomics by insulin and the promotion of glucose-lipid metabolism with extended duration - Xiangli Zhang; Pengfei Du; Ziyang Wang; Yao Zhu; Xuemeng Si; Wen Chen; Yanqun Huang (Poultry Science)
Birds' glycolipid metabolism has garnered considerable attention due to their fasting blood glucose levels being nearly twice those of mammals. While skeletal muscle is the primary insulin-sensitive tissue in mammals, the effects of insulin on chicken skeletal muscle remain unclear. In this study, the insulin-responsive metabolites were identified in broiler's pectoralis muscle (after 16 h of fasting) using widely targeted metabolomics. Glycolipid concentrations were measured using kits, and the expression of key genes involved in glucose metabolism was assessed via quantitative real-time PCR (qRT-PCR). The insulin tolerance test, performed by injecting 5 IU/kg body weight of insulin, demonstrated a rapid drop in blood glucose levels from 0 to 15 min, with a consistent reduction observed at 120 min (P < 0.01). Insulin did not alter glucose and glycogen content in chicken pectoralis; however, low-density lipoprotein (LDL, P < 0.05) levels were upregulated in the early phase (15 min). With an extended insulin duration (120 min), pectoralis glucose content increased (P < 0.05), accompanied by a reduction in TG levels (P < 0.05). Metabolomic analysis revealed that insulin promotes the downregulation of 63 out of 71 metabolites at 15 min and the upregulation of 101 out of 134 metabolites at 120 min, mainly associated with lysine degradation and thyroid hormone signaling pathways, respectively. 7 metabolites were dynamically modulated in the same manner over time (2 up-up and 5 down-down). Early insulin inhibited glycolysis, evidenced by the reduction in phosphoenolpyruvate levels and hexokinase 2 (HK2) expression; however, insulin promoted glucose uptake through the activation of glucose transporter 4 (GLUT4) and enhanced glycolysis, accompanied by elevated fatty acid metabolism at the later phase.In conclusion, insulin dynamically regulates the metabolomics of the pectoralis muscle over time. Initially, chicken muscle tissues downregulate metabolic activities to accommodate the new signaling state, followed by significant upregulation to meet heightened metabolic demands. Extended insulin monitoring promotes glucose uptake and glycolysis, alongside enhanced fatty acid metabolism. This research provides insights into the potential mechanisms of insulin action in chicken muscles.